2014
DOI: 10.1007/s11121-014-0473-3
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Level Approach to Promoting Healthy Child Development and School Success in Low-Income, Urban Neighborhoods: Impact on Parenting and Child Conduct Problems

Abstract: Minority children living in disadvantaged neighborhoods are at high risk for school dropout, delinquency and poor health, largely due to the negative impact of poverty and stress on parenting and child development. This study evaluated a population-level, family-centered, school-based intervention designed to promote learning, behavior and health by strengthening parenting, early childhood classroom quality, and child self-regulation during early childhood. Ten schools in urban districts serving primarily low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 36 publications
1
63
0
Order By: Relevance
“…ParentCorps was built on an extensive body of cross-cultural parenting and child developmental research (Bradley & Corwyn, 2005; Lawire, 2009), and includes three core components: Professional Development (PD) for school-based staff to increase knowledge and use of EBPs in the classroom and to support strong home-school connections; and Programs for Parents and Students to promote EBPs at home and children’s social emotional and behavior regulation skills. In two school cluster randomized controlled trials (RCTs) in New York City, the multi-component ParentCorps has been shown to be highly acceptable to culturally diverse low-income populations and has yielded robust and sustained effects on targeted teacher/classroom, parent and child outcomes (Cohen’s ds ranged from .42 –.85 for teacher outcomes, .16–.50 for parent outcomes, and .24–.81 for child outcomes)(Brotman et al, 2011; Brotman et al, 2012; Brotman et al, 2016; Dawson-McClure et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…ParentCorps was built on an extensive body of cross-cultural parenting and child developmental research (Bradley & Corwyn, 2005; Lawire, 2009), and includes three core components: Professional Development (PD) for school-based staff to increase knowledge and use of EBPs in the classroom and to support strong home-school connections; and Programs for Parents and Students to promote EBPs at home and children’s social emotional and behavior regulation skills. In two school cluster randomized controlled trials (RCTs) in New York City, the multi-component ParentCorps has been shown to be highly acceptable to culturally diverse low-income populations and has yielded robust and sustained effects on targeted teacher/classroom, parent and child outcomes (Cohen’s ds ranged from .42 –.85 for teacher outcomes, .16–.50 for parent outcomes, and .24–.81 for child outcomes)(Brotman et al, 2011; Brotman et al, 2012; Brotman et al, 2016; Dawson-McClure et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…All procedures were specified in manuals, and multimethod assessments indicated that fidelity was high (after capacity building, adherence was ≥90% 10 ). Most families (257 of 423 [60.8%]) participated and, among participants, mean attendance was 7.30 of 13.…”
Section: Methodsmentioning
confidence: 99%
“…These studies overwhelmingly reported that, after completion of the programmes, participating parents remained successfully involved in their children's education (Dawson-McClure et al, 2015;Reece et al, 2013). They also showed a significant effect of the programmes on children's reading and writing skills, as well as parents' strategies to help children read (Sylva et al, 2008).…”
Section: Empirical Papersmentioning
confidence: 99%